New molecules in the therapy of chronic graft-versus-host disease: hematopoietic stem cell transplantation - Steiner, Laurenz; Klein, Stefan; Kreil, Sebastian (Current opinion in hematology, 2025)
Purpose of review - Chronic graft-versus-host disease (cGvHD) remains a major complication following allogeneic hematopoietic cell transplantation, frequently requiring multiple lines of immunosuppressive treatment. The increasing approval of targeted therapies demands an updated understanding of their clinical positioning, strengths, and safety considerations. - Recent findings - Several agents have been approved for cGvHD following treatment failure, including ibrutinib and ruxolitinib after first line, and belumosudil and axatilimab after at least two prior therapies. Novel compounds such as ivarmacitinib, TDI-01, rovadicitinib, and pimicotinib target distinct or combined inflammatory and fibrotic pathways and demonstrate promising efficacy across multiple organ systems. However, safety profiles and organ-specific response rates vary. Prior exposure to Janus kinase inhibitors influences therapeutic sequencing, while discrepancies between formal and patient-reported outcomes represent challenges for data interpretation. - Summary - Expanding therapeutic options in cGvHD require decision-making based on organ involvement, prior therapy, and tolerability. Emerging compounds offer the potential to modulate chronic inflammation and fibrosis more precisely, supporting a move toward personalized and combinatorial approaches in advanced-line settings.